A course in English for occupational purposes at the International Islamic University Malaysia : meeting the English language needs of the industry - Mechraoui, Amal (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
Malaysian higher education institutions have been urged to adequately prepare their graduates for the increasingly competitive job market because employers have expressed concerns about the wide disparity between the communication skills in English for job applicants and the English language competency required for employment. In view of the importance of English proficiency as a critical employability skill, there is a need to assess the language outcomes of English for Occupational Purposes courses offered by Malaysian higher education institutions. This study examines whether the English for Occupational Purposes course (LE 4600), which is one of the English for Specific Purposes courses offered for students of the Kulliyyah of Economics and Management Sciences at the International Islamic University Malaysia (IIUM) is meeting its intended language outcomes. This study also investigates whether the language outcomes of the course are compatible with the language needs of the industry. To this end, the objective –based evaluation model developed by Owen (2007) was used for the purpose of the study. A multi-method approach was adopted to address the objectives of the study. Research methods comprised descriptive and quantitative methods to scientific inquiry. Specifically, data were collected using triangulated sources comprising programme providers, students, and course lecturers and triangulated methods comprising document analysis, survey questionnaires, and semi-structured interviews. While data gathered from the questionnaires were analyzed using frequency counts and percentages and were tabulated, data collected from interviews and document analysis were summarized and interpreted in a descriptive manner. The findings of the study reveal that generally most of the respondents perceived the course as meeting its intended language outcomes. However, some minor weaknesses in the EOP course in terms of teaching methodology and lack of practical application were identified. Secondly, it is discovered that the language outcomes of the course were not consistent with the needs of the industry. The findings therefore indicate a need to revise several aspects of the course based on the current needs of the students as well as the needs of the industry.